Google Web toolkit 2 application development cookbook : over 70 simple but incredibly effective practical recipes to develop web applications using GTW with JPA, MySQL and iReport - Ahammad, Shamsuddin (Quick answers to common problems., 2010)
Over 70 simple but incredibly effective practical recipes to develop web applications using GWT with JPA, MySQL and i Report.